2002
DOI: 10.1038/sj.onc.1205126
|View full text |Cite
|
Sign up to set email alerts
|

HOXD3 enhances motility and invasiveness through the TGF-β-dependent and -independent pathways in A549 cells

Abstract: Homeobox genes regulate sets of genes that determine cellular fates in embryonic morphogenesis and maintenance of adult tissue architecture by regulating cellular motility and cell-cell interactions. Our previous studies showed that a speci®c member, HOXD3, when overexpressed, upregulates integrin b3 expression in human erythroleukemia HEL cells and lung cancer A549 cells, and enhances their motility and invasiveness. We performed a microarray study of over 7075 genes to determine the mechanisms underlying the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 48 publications
2
36
0
3
Order By: Relevance
“…However, the present study has not shown any significant change in expression in either of these genes. These results might be partly explained by the choice of cell type in the present study, and partly due of the activity of other signal pathways, such as the Ras and ERK pathway for cyclin D1 regulation (Pruitt and Der, 2001;Jirmanova et al, 2002), TGF-b and hepatocyte growth factor for CD44 regulation (Miyazaki et al, 2002;Mine et al, 2003).…”
Section: Discussionmentioning
confidence: 85%
“…However, the present study has not shown any significant change in expression in either of these genes. These results might be partly explained by the choice of cell type in the present study, and partly due of the activity of other signal pathways, such as the Ras and ERK pathway for cyclin D1 regulation (Pruitt and Der, 2001;Jirmanova et al, 2002), TGF-b and hepatocyte growth factor for CD44 regulation (Miyazaki et al, 2002;Mine et al, 2003).…”
Section: Discussionmentioning
confidence: 85%
“…12 Our previous studies showed that human lung cancer A549 cells transfected with HOXD3 gene acquired more metastatic, invasive and motile phenotypes. 13,14 We also observed that the transduction of HOXD3-antisense expression vectors into human melanoma cells dramatically diminished their invasive and motile activities. 15 Taken together, inappropriate expression of a particular HOX gene(s) is likely involved in tumor development and malignant progression such as invasion and metastasis and that the HOX gene(s) responsible for oncogenesis and/or tumor progression differs according to the organs or tissues from which the tumor cells have derived.…”
mentioning
confidence: 74%
“…As previously shown, HOXD3-overexpressing A549 cells convert latent TGF-beta into active one, which activates the TGF-β-signaling in an autocrine manner [32].…”
Section: Hoxd3-transfectants Fibronectin Is a Ligand For A Variety Omentioning
confidence: 89%
“…The stimulation with TGF-β enhances haptotaxis of A549 cells to type I collagen but not to vitronectin, fibrinogen or fibronectin [32]. Thus we suppose that HOXD3 enhances cell motility through the TGF-β-dependent and -independent pathways in A549 cells.…”
Section: Hoxd3-transfectants Fibronectin Is a Ligand For A Variety Omentioning
confidence: 92%
See 1 more Smart Citation